Ultrasound measurement of renal size in newborn infants. - Scott, J E (1990)
Renal measurements were made by ultrasonography in 560 healthy newborn infants. Three dependent variables (kidney length, kidney depth, and kidney area) were measured, together with three independent variables (birth weight, head circumference, and gestational age). The SD of the measurement inconsistency was 0.13 cm for length, 0.078 cm for depth, and 0.32 cm2 for area; the percentages of total variance caused by measurement inconsistency were 7.9, 9.5, and 7.5, respectively. There was a significant difference between right and left kidneys in length and depth for each independent variable. The left kidney increased more in length and less in depth than the right so that the areas remained similar as the scale of variable increased. Kidney depth and area in boys were significantly larger than in girls, both dimensions increasing at equal rates. Centile charts for each dependent variable by each independent variable were constructed by a non-parametric method.